Chromatographic and mass spectrometric characterization of essential oils and extracts from Lippia (Verbenaceae) aromatic plants (2012)
Analytical methodologies based on GC and HPLC were developed for the separation and quantification of carnosic acid, ursolic acid, caffeic acid, p-coumaric acid, rosmarinic acid, apigenin, luteolin, quercetin, kaempferol, naringenin, and pinocembrin. These methods were used to characterize essential oils and extracts obtained by solvent (methanol) and by supercritical fluid (CO2) extraction from stems and leaves of Lippia (Verbenaceae family) aromatic plants (Lippia alba, Lippia origanoides, Lippia micromera, Lippia americana, Lippia graveolens, and Lippia citriodora). Supercritical CO2 extraction isolated solely pinocembrin and narigenin from three L. origanoides chemotypes. Solvent extracts possessed a more varied composition that additionally included apigenin, quercetin, and luteolin. Solvent extraction afforded higher overall flavonoid yields from all species in comparison with supercritical CO2 extraction. Pinocembrin was determined in L. origanoides extract at a concentration of 30 mg/g of plant material, which is more than ten times higher than the amount at which polyphenols are regularly found in aromatic plant extracts.